2022
DOI: 10.1007/s12274-022-4351-1
|View full text |Cite
|
Sign up to set email alerts
|

Sensitively detecting antigen of SARS-CoV-2 by NIR-II fluorescent nanoparticles

Abstract: Early detection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is an efficient way to prevent the spread of coronavirus disease 2019 (COVID-19). Detecting SARS-CoV-2 antigen can be rapid and convenient, but it is still challenging to develop highly sensitive methods for effective diagnosis. Herein, a lateral flow assay (LFA) based on fluorescent nanoparticles emitting in the second near-infrared (NIR-II) window is developed for sensitive detection of SARS-CoV-2 antigen. Benefiting fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…Hu and his colleagues fabricated NIR-II nanoparticles by encapsulating organic dyes in polyethylene and used them as a sensing platform for the rapid detection of the SARS-CoV-2 antigen. The biosensor possesses a wide analytical range of 0.02–120 ng/mL, and the LOD is 0.01 ng/mL, which cannot be compared with traditional colloidal gold technology [ 50 ]. These results suggest that the NIR-II biosensor with enhanced performances is suitable for mass screening.…”
Section: Fluorescence Biosensor For Sars-cov-2 Diagnosismentioning
confidence: 99%
“…Hu and his colleagues fabricated NIR-II nanoparticles by encapsulating organic dyes in polyethylene and used them as a sensing platform for the rapid detection of the SARS-CoV-2 antigen. The biosensor possesses a wide analytical range of 0.02–120 ng/mL, and the LOD is 0.01 ng/mL, which cannot be compared with traditional colloidal gold technology [ 50 ]. These results suggest that the NIR-II biosensor with enhanced performances is suitable for mass screening.…”
Section: Fluorescence Biosensor For Sars-cov-2 Diagnosismentioning
confidence: 99%
“…The NP antigen of SARS-CoV-2 has been proven more conserved than other structural proteins including Spike antigen [30,31]. Previous studies have demonstrated that highly sensitive and specific detection of SARS-CoV-2 can be achieved by using NP as target antigen [32][33][34]. Thus, we chose NP as target for SARS-CoV-2 detection.…”
Section: Lfamentioning
confidence: 99%
“…Currently, the most commonly used analytical methods for SARS-CoV-2 detection are RT-qPCR, serological assays, and paper-based sensors, such as lateral flow kits. 13 15 RT-qPCR requires expensive instruments, sophisticated operations, and professionals to conduct the experiment for more than 6 h, limiting its field use. 16 Although serological methods can be completed in a short time and require no complicated equipment, their low sensitivity to mild and asymptomatic infections and long time to produce an antibody response restrict their utilization in WBS.…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of the WBS approach for developing a warning system and a consequent effective intervention system requires a rapid analytical method for the on-site detection of SARS-CoV-2 in wastewater collection points. Currently, the most commonly used analytical methods for SARS-CoV-2 detection are RT-qPCR, serological assays, and paper-based sensors, such as lateral flow kits. RT-qPCR requires expensive instruments, sophisticated operations, and professionals to conduct the experiment for more than 6 h, limiting its field use . Although serological methods can be completed in a short time and require no complicated equipment, their low sensitivity to mild and asymptomatic infections and long time to produce an antibody response restrict their utilization in WBS. , Herein, lateral flow kits developed via serological methods are also not suitable for WBS.…”
Section: Introductionmentioning
confidence: 99%